Community Education Program on Household Food Storage and Logistics Management to Support Stunting Prevention - Rahmi M Nur; Yovita Yulia M. Zai; Rini Syahfitri; Inang Suryani; Refki Riyantori; Anisa Jasmiarlita Muluk (Journal of Social and Community Service, 2026)
Stunting remains a major public health challenge in Indonesia and is influenced not only by nutritional adequacy but also by effective household food management. However, education on food storage and household food management based on logistics principles remains limited. This community service program aimed to improve the knowledge and skills of pregnant women, breastfeeding mothers, and families with children under five in applying household food storage and management practices to support stunting prevention. The program was implemented through the Nagari Emas (NGE) Stunting Reduction Acceleration Program in the working area of Pakan Rabaa Community Health Center, Lima Puluh Kota Regency, using a participatory educational approach that included basic health screening, interactive counseling, group discussions, educational games, and pocketbook distribution. The educational materials covered proper food storage, implementation of the First In, First Out (FIFO) principle, nutritious meal planning, and effective food purchasing strategies. The program improved participants' knowledge and awareness of household food logistics management in maintaining food quality, reducing food waste, and supporting family nutritional adequacy. This program has the potential to serve as a sustainable logistics-based educational model for stunting prevention.